An Optimal Scheduling Controller for Virtual Power Plant and Microgrid Integration Using the Binary Backtracking Search Algorithm - Abdolrasol M.G.M.; Hannan M.A.; Mohamed A.; Amiruldin U.A.U.; Abidin I.B.Z.; Uddin M.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Bins; Controllers; Fueling; Gas generators; Global optimization; Health; Integration; Learning algorithms; Optimization; Particle swarm optimization (PSO); Power generation; Reliability; Renewable energy resources; Scheduling; Wind; Backtracking search algorithms; Micro grid; Optimal scheduling; Scheduling controllers; Virtual power plants; Wind speed; Power control